DIMENSI EKONOMI POLITIK DAN SPASIAL KONSUMSI LISTRIK SELURUH PROVINSI INDONESIA - , TIMOTIUS DHARMAWAN HARSONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One of the most striking issues is that electricity capacity growth in Indonesia has lagged behind the pace of electricity demand growth, leading to power shortages and a low electrification ratio. This study attempts to prove the causal relationship between electricity comsumption and economic growth (1944- 2010) and to explore some economic and spatial patterns of electricity consumption (1993-2010) in 14 PLNâs distributive regions and 6 economic corridors. Apart of that, a political economic analysis on electricity tariff policy is also performed based on quantitative and qualitative data collected during indepth interview and snow ball sampling technique. Using modified Granger causality tests with Error Correction Model (ECM) and time series data within the period of 1984-2010, the findings shows that there is a unidirectional short run relationship moving from electricity consumption to GDP per capita for Indonesia. The causality test for Sumatra corridor also shows the same result as Indonesia. However, the causality of Kalimantan corridor shows the opposite direction of Indonesiaâs and Sumatra economic corridorâs. Typology and discriminant analyses prove to be useful as the basis to integrate the formulation of regional electricity development policy. More importantly, Indonesia can enhance the performance of regions by taking into account the spatial dimension of population, industrialization, electricity development and poverty. The findings in this study offer some insights about spatial aspect of the Indonesiaâs electricity consumption and regional economies which do carry some implication on regional development. By applying economic and spatial dimension, this analysis pioneers the study of Indonesiaâs electricity consumption that incorporates geography into electricity and regional development policy. Based on the findings, further analysis are performed from the perpective of the political economic to understand why the electricity tariff accross all regions in Indonesia is set to be homogeneous, regardless of the fact that economic and characteristic among regions are proven to be different. Finally, the findings suggest that fundamental changes in electricity and regional development policies are required. More importantly, Indonesia needs electricity and development policy that incorporate regional variations in terms of population, industrialisation, electricity development and poverty to enhance the performance of regions by taking into account the spatial dimension of dominant factors in terms of electric consumption and economic growth. The findings and the analysis in this study offer some insights about spatial and political economic aspect of the Indonesiaâs electricity consumption and regional development. Keywords: electricity consumption, economic growth, Granger Causality, discriminant model, typology, region, electricity tariff and subsidy.